Successful Treatment of Crizotinib-Induced Fulminant Liver Failure: A Case Report and Review of Literature - Kyle Kreitman; Satheesh P. Nair; Jiten P. Kothadia (Case Reports in Hepatology)
Crizotinib is a first-line tyrosine kinase inhibitor used for the treatment of metastatic lung cancer. Crizotinib-induced hepatotoxicity is a rare event. We report a case of a 46-year-old female with a history of metastatic lung cancer who presented with acute liver failure after being on crizotinib for two months. The medication was discontinued, and she was treated with N-acetylcysteine for seven days. Her liver function tests returned to normal limits after 26 days after admission. The precise mechanism and risk factors of crizotinib-induced hepatotoxicity remain unknown. Physicians should be aware of the potentially lethal side effect caused by crizotinib.